Proses Pengambilan Keputusan Pembelian Produk di Aplikasi TikTok pada Generasi Z - Putri, Nadhira Halizah; Alfian, Ilham Nur (Universitas Airlangga, 2024)
This qualitative study aims to explore the picture of product purchase decision-making through the TikTok application in Generation Z. Using a case study approach, this study explores the subjective experiences of individuals in the process. Through a criterion-based technique, participants aged 16-22 years with TikTok accounts and online purchase experiences were selected. Data were collected through interviews, focusing on identifying key themes in decision-making. The findings show that factors such as desire, impulsive behavior, confidence, information search, and features within the TikTok app influence the decision-making process. Participants felt satisfied after successfully buying, but felt dissatisfied when financial limitations prevented the desired purchase.